Cyber Bullying Detection In Hinglish Language On Social Media - Upadhyay, Anurag; Maheshwari, Manish (International Journal of Computer Sciences and Engineering, 2025)
Now a day, most of people are using twitter, face book and micro blogging sites. They share their opinion, feeling for particular topic through comment, review. The volume of data generated daily is very large. So, it is important to analyse the data for gaining information from that. Sentimental analysis is used for mining various types of data for opinion through text analytics. It can be negative, positive or impartial. Twitter became one of the largest platform for people to show their opinion, share their thoughts and consistently updated about any organization, events etc. So, data collected is huge somewhat called big data. To process such a big data we need framework that manages this entire thing. In this paper, we attempt to perform cyber bullying detection in a supervised way by proposing a learning framework. More specifically, we first investigate whether sentiment information is correlated with cyber bullying behavior.